Theoretical Justification of the Forces Generated on the Cylinder Surface of a Double Row Cat (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The quality of tillage directly depends on the agricultural machinery used. Thus, the development of new effective agricultural machinery makes it possible to increase the productivity of cultivated crops. “An important technological operation of the soil cultivation process is rolling. With high-quality implementation of this technological operation, the yield of grown crops increases. This technological operation is used in all climatic zones for all types of soil to ensure optimal soil density and structure according to agricultural requirements.” Rolling is carried out using soil-cultivating rollers and special tools, but the known designs do not fully meet agrotechnical requirements.